Shallow-water black corals (Cnidaria: Anthozoa: Hexacorallia: Antipatharia) from SW Madagascar - Terrana, Lucas; Bo, Marzia; Opresko, Dennis M.; Eeckhaut, Igor (Zootaxa, 2020)
Antipatharians, also known as black corals, represent a small group of anthozoan hexacorallians found in all oceans of the world. They are generally considered a deep-water taxon; however, some of the most diverse communities are known from tropical shallow waters. With a few poorly detailed exceptions, shallow-water black corals from the Indian Ocean and especially those from Madagascar are mostly unknown. In this study, we report for the first time a highly diverse black coral assemblage of the Western Indian Ocean thriving in shallow waters and upper mesophotic depths (10–52 m depth) along the SW coast of Madagascar. A total of 22 species belonging to six genera (Antipathes, Arachnopathes, Cirrhipathes, Cupressopathes, Myriopathes and Stichopathes) and two families (Antipathidae and Myriopathidae) are described, of which 20 are found in the northern pass of the Great Reef of Toliara, thus representing the most diverse site of the areas investigated. Most of the shallow-water species from the Indian Ocean were originally described more than a century ago, sometimes without being reported again until now. All the descriptions herein rely solely on morphology and include detailed in situ pictures and scanning electron microscope images, in addition to range expansions for many species.